2006
DOI: 10.5188/ijsmer.13.132
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Solid-phase Extraction with Electrothermal Atomic Absorption Spectrometry for Determination of Trace Elements

Abstract: An enrichment step in a sample treatment is essential for trace analysis to improve the sensitivity and to eliminate the matrix of the sample. Solid-phase extraction (SPE) is one of the widely used enrichment technique. Electrothermal atomic absorption spectrometry (ETAAS) is a well-established determination technique for trace elements. The integration of SPE with ETAAS leads to further improvement of sensitivity, an automation of the measurement and the economy in the sample size, amounts of the reagents and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Various solid phase adsorbents including C 18 -bonded silica gel (Starvin et al 2004), organic chelating resin (Unsworth et al 2001), ac tivated carbon (Nukatsuka and Ohzeki 2006), activated oxide (Pu et al 2004), thermally-modified kaolinite (Afzali et al 2005) and zeolite (Mostafavi et al 2006) have been proposed for this technology. Various solid phase adsorbents including C 18 -bonded silica gel (Starvin et al 2004), organic chelating resin (Unsworth et al 2001), ac tivated carbon (Nukatsuka and Ohzeki 2006), activated oxide (Pu et al 2004), thermally-modified kaolinite (Afzali et al 2005) and zeolite (Mostafavi et al 2006) have been proposed for this technology.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Various solid phase adsorbents including C 18 -bonded silica gel (Starvin et al 2004), organic chelating resin (Unsworth et al 2001), ac tivated carbon (Nukatsuka and Ohzeki 2006), activated oxide (Pu et al 2004), thermally-modified kaolinite (Afzali et al 2005) and zeolite (Mostafavi et al 2006) have been proposed for this technology. Various solid phase adsorbents including C 18 -bonded silica gel (Starvin et al 2004), organic chelating resin (Unsworth et al 2001), ac tivated carbon (Nukatsuka and Ohzeki 2006), activated oxide (Pu et al 2004), thermally-modified kaolinite (Afzali et al 2005) and zeolite (Mostafavi et al 2006) have been proposed for this technology.…”
mentioning
confidence: 99%
“…It should be noted that the investigation of adsorbents plays a key role in the development of SPE. Various solid phase adsorbents including C 18 -bonded silica gel (Starvin et al 2004), organic chelating resin (Unsworth et al 2001), ac tivated carbon (Nukatsuka and Ohzeki 2006), activated oxide (Pu et al 2004), thermally-modified kaolinite (Afzali et al 2005) and zeolite (Mostafavi et al 2006) have been proposed for this technology. In our previous work, an adsorbent of N-benzoyl-N-phenylhydroxylamine (BPHA) loaded on microcrystalline naphthalene was prepared for the speciation of Fe(II) and Fe(III) (Xiong et al 2006).…”
mentioning
confidence: 99%
“…1 The methods in which the small volume of eluent or resin slurry from a packed column or a renewable column are directly injected into the ETAAS are well established, and many applications have been reported. [2][3][4] However, there is a danger of column plugging, and the small amounts of sorbent sometime lead to a low efficiency for the extraction.…”
mentioning
confidence: 99%
“…Among various techniques reported so far, solid phase extraction is conveniently utilized for separation/preconcentration of trace elements in various samples. [10][11][12][13] In LEP-AES determination, only the solid phase extraction using Meta SEP AnaLig PB-01 was applied to the separation/preconcentration of lead in the soil-extracted solution. 9 We previously reported that a chelate resin immobilizing carboxymethylated pentaethylenehexamine (CM-PEHA resin) is excellent for separation/preconcentration of trace elements in water samples.…”
Section: Introductionmentioning
confidence: 99%